International biobanking: overview of key practices and policies - Vaught, Jim (Henry Stewart Talks, 2016)
Biobanking basics: best practices, infrastructure, quality management, International efforts to develop and harmonize best practices, Controlling variability: critical to international exchange of specimens and data, Biobanking networks and factors for success, Economics and sustainability, Current hot topics in international biobanking, Additional resources: biobanking organizations, web sites, publications
Archived at 2022/06/30